Ground topography validation of a high-resolution DEM and orthophotos obtained with a commercial UAS - Peralta, Cristian; Beriain, Eneko; Iglesias, Claudio; Marangunic, Cedomir; Marangunic, Andres; Casassa, Gino (My University, 2017)
A commercial Unmanned Aircraft System (UAS) flying at a height above ground of 135 m has been deployed over a 0.5 × 1 km village area at the foothills of the central Andes of Chile in order to obtain a 3D survey map of the area. A high resolution Digital Elevation Model (DEM) was derived from a total of 273 aerial photos by means of the structure from motion software Pix4D. The DEM was georeferenced based on the absolute coordinates of 6 Ground Reference Points (GRPs). Comparison of the DEM elevations with a precise kinematic dual-frequency GNSS ground survey yields a mean height difference of 12 cm and a standard deviation of 5 cm. Planimetric precision of the orthophoto mosaic is in average 1 cm when compared to ground measurements obtained with a tape measure on small-scale landmarks. Comparison of the 3D coordinates of the orthophotos and the DEM with 4 Ground Control Points shows that the horizontal accuracy is better than 5 cm and the vertical accuracy is better than 12 cm. The results confirm that accurate topographic information can be derived from aerial photographs obtained with a drone equipped with a GNSS receiver.
Keywords: digital elevation model (dem); drone; gnss (global navigation satellite system); unmanned aircraft system (uas)